Using survey data on population health literacy for developing a National Action Plan in Germany. (13th November 2019) - Berens, E; Schaeffer, D
Abstract: Promoted by the results of the European Health Literacy survey, the first representative German Health Literacy Survey (HLS-GER) was conducted in 2014. The results showed that every second individual in Germany (54.3 %) has limited health literacy. Thus, a majority of the German population is confronted with difficulties in finding, understanding, appraising, and applying health information. Particularly, vulnerable groups as people with migration background, low education attainment, and in older age as well as chronically ill have even more problems in processing health information and thus are confronted with challenges to maintain health, prevent diseases and use the healthcare system. Based on the initial research findings of the HLS-GER and the increasing attention and discussions arising with its results, the National Action Plan Health Literacy was developed by a group of experts to systematically improve and strengthen health literacy in Germany. After agreements with representatives of politics and society, health professions and patient and citizen organizations it was published in 2018. It includes 15 specific recommendations in four areas of action and focusses on fostering health literacy in daily life, creating a user-friendly and health literate healthcare system, HL and chronic illness and expanding health literacy research. Five underlying key principles are mentioned to consider in implementing the National Action Plan. The HLS-GER survey data were further used to discuss some recommendations within specialized workshops leading to more detailed strategy papers. The current political and practical developments and discussions initiated by National Action Plan, will be picked up in the second German Health Literacy Survey (HLS-GER2), which is part of HLS19. By repeatedly assessing population HL in Germany the implementation of the National Action Plan can be monitored and further specified, thus survey data help to create policy.